Analisis Materi Sistem Periodik Unsur Pada Buku Teks Kimia SMA/MA Kelas X - Anipah Anipah; Abdul Hadjranul Fatah; Syarpin Syarpin (FKIP Universitas Palangka Raya, 2020)
This research is a type of descriptive research with a qualitative research approach. The objects of this research are (1) Class X chemistry textbooks, writer Superior Sudarmo published by Erlangga in 2013 (2) Class X chemistry textbooks by Endang-Tarti Harjani, published by PT. Wangsa Jatra Lestari in 2016. This research was conducted by analyzing the periodic system material of elements in each book, analyzing the suitability of book A's concept label to book B, analyzing the macro discourse structure in books A and B, analyzing the chemical representation and analyzing the concept book's book A and B for the 2013 Curriculum. The results show that Books A and B have a pretty good concept suitability for the 2013 Curriculum and only isotope, isotope, and isobar material are not presented. The topic in book A is the Periodic System of Elements, while in book B the periodic table of elements. In books A and B both have symbolic representation criteria.